Chemical speciation and potential mobility of heavy metals in the soil of former tin mining catchment - Ashraf, M.A.; Maah, M.J.; Yusoff, I. (Hindawi Publishing Corporation, 2012)
This study describes the chemical speciation of Pb, Zn, Cu, Cr, As, and Sn in soil of former tin mining catchment. Total five sites were selected for sampling and subsequent subsamples were collected from each site in order to create a composite sample for analysis. Samples were analysed by the sequential extraction procedure using optical emission spectrometry (ICP OES). Small amounts of Cu, Cr, and As retrieved from the exchangeable phase, the ready available for biogeochemical cycles in the ecosystem. Low quantities of Cu and As could be taken up by plants in these kind of acidic soils. Zn not detected in the bioavailable forms while Pb is only present in negligible amounts in very few samples. The absence of mobile forms of Pb eliminates the toxic risk both in the trophic chain and its migration downwards the soil profile. The results also indicate that most of the metals have high abundance in residual fraction indicating lithogenic origin and low bioavailability of the metals in the studied soil. The average potential mobility for the metals giving the following order: Sn > Cu > Zn > Pb > Cr > As.